Hubungan Pengetahuan dengan Perilaku Pengelolaan Limbah Rumah Tangga Kelurahan Tipulu Tahun 2026 - Siti Rabbani Karimuna; Alda Agresiya; Husnul Amalia; Inggi Pratiwi; Melinda Septiani; Mildah Mildah (Lembaga Pengembangan Kinerja Dosen, 2026)
Household waste is solid waste generated from daily human activities and domestic processes within households. This study aims to analyze the relationship between community knowledge and household waste management behavior in Tipulu Village. The research applied a descriptive quantitative approach involving 30 respondents selected through simple random sampling. Data were collected using questionnaires and analyzed using the Chi-Square test. The findings showed a p value of 0.062, indicating that there was no significant relationship between community knowledge and household waste management behavior in Tipulu Village. Most respondents demonstrated good knowledge regarding waste management; however, their behavior in managing household waste remained only moderate. This condition was influenced by several factors, including habitual practices, limited waste management facilities, low motivation, and insufficient environmental support. The study highlights that knowledge alone is not enough to encourage proper waste management behavior. Therefore, increased environmental education, community awareness programs, and government support in providing adequate waste management facilities are necessary to create a clean, healthy, and sustainable environment.